Práticas de produção de textos escritos no ensino técnico integrado ao médio - Milanezi, Cynthia Nunes (2011)
This paper is part of the studies developed by the research group Literacy, Reading and Writing, linked to the research branch Education and Languages, of the PostGraduation course of Education of the Federal University of Espírito Santo. This work is aimed at analyzing the practices of written text production in a second year group of High School integrated to the Technical teaching, from the proposals of the teacher and the student’s answers to these proposals. In order to accomplish this objective, we adopted the qualitative case study, using as methods and techniques of data collecting and production the document analysis, the participative observation, interviews, audio recording, digital camera pictures and camcorder. The data was analyzed based on Bakthin (2003, 2006) tenets on text and language, on the conditions outlined by Geraldi (2003, 2006) for as effective text production, and the considerations of Charaudeau (2010) on ways of organizing the discourse. During the analysis, the research tries to investigate the conditions of text production, as well as analyze the proposals presented to the students and the texts produced by them. This research noted that the teacher’s work was based on the notion of types or modes of textual organization of discourse, which were chosen because of the purpose of the technical course. It concludes that, although the individuals faced proposals which imposed speech restrictions, they effectively could be placed as authors of their texts, responsible for their sayings. It also noted that these activities give students a space for emerging opinions, feelings, outbursts and even complaints. As the studies of Geraldi (2003), this research recognizes that text production can be part of a learning process of knowledge and production, not of recognition and reproduction. Therefore, it is necessary that the practices are related to the individual’s lives, to make the work with texts, and with the language in general, more productive and meaningful for teachers and students.